KOMPARASI HUKUMAN BAGI NARAPIDANA NARKOTIKA DALAM PERSPEKTIF HUKUM PIDANA PENITENSIER: STUDI PERBANDINGAN INDONESIA DAN MALAYSIA : (COMPARATIVE ANALYSIS OF SENTENCING FOR NARCOTICS OFFENDERS IN THE PERSPECTIVE OF PENITENTIARY CRIMINAL LAW: A STUDY OF INDONESIA AND MALAYSIA) - Dwi Pramesti, Febrina (Cahaya Ilmu Bangsa, 2025)
Abstract The issue of narcotics in Indonesia and Malaysia presents a significant challenge in criminal law. Indonesia enforces Law Number 35 of 2009, which still focuses on imprisonment for both drug users and traffickers. Meanwhile, Malaysia applies the Dangerous Drugs Act 1952, which clearly distinguishes between addicts and traffickers and prioritizes rehabilitation for addicts. This difference highlights Indonesia’s struggle to classify drug users as either victims or offenders, whereas Malaysia has a more systematic approach. This study aims to compare sentencing policies in both countries to find more effective solutions for handling drug-related cases. The findings indicate that Malaysia emphasizes rehabilitation for addicts before imposing penalties, while Indonesia continues to prioritize criminal punishment. Additionally, Malaysia has clear quantity limits to differentiate between users and traffickers, whereas Indonesia lacks a precise legal threshold. As a result, many drug users in Indonesia receive prison sentences without considering health-based approaches. Therefore, a more balanced policy is needed so that Indonesia can strictly punish drug traffickers while also providing protection for addicts through more effective rehabilitation. With a more structured system, Indonesia can reduce recidivism rates and establish a more humane legal framework without diminishing the deterrent effect on drug-related offenders. Keywords: Narcotics, criminal law, sentencing, rehabilitation, legal comparison. Abstrak Permasalahan narkotika di Indonesia dan Malaysia menjadi tantangan besar dalam hukum pidana. Indonesia menerapkan Undang-Undang Nomor 35 Tahun 2009 yang masih berfokus pada hukuman penjara bagi pengguna dan pengedar narkotika. Sementara itu, Malaysia menggunakan Dangerous Drugs Act 1952 yang membedakan secara tegas antara pecandu dan pengedar serta lebih menekankan rehabilitasi bagi pecandu. Perbedaan ini menunjukkan bahwa Indonesia masih menghadapi kendala dalam memilah pengguna sebagai korban atau pelaku, sedangkan Malaysia memiliki aturan yang lebih sistematis. Penelitian ini bertujuan untuk membandingkan kebijakan pemidanaan di kedua negara guna mencari solusi yang lebih efektif dalam menangani kasus narkotika. Hasil penelitian menunjukkan bahwa Malaysia lebih mengutamakan rehabilitasi bagi pecandu sebelum memberikan hukuman, sedangkan Indonesia masih menjadikan hukuman pidana sebagai langkah utama. Selain itu, Malaysia memiliki batasan kuantitas narkotika yang jelas untuk membedakan pengguna dan pengedar, sementara Indonesia belum mengatur batasan ini secara tegas. Akibatnya, banyak pengguna di Indonesia yang langsung dijatuhi hukuman penjara tanpa mempertimbangkan pendekatan kesehatan. Oleh karena itu, diperlukan kebijakan yang lebih seimbang agar Indonesia dapat menindak tegas pengedar narkotika sekaligus memberikan perlindungan bagi pecandu melalui rehabilitasi yang lebih efektif. Dengan sistem yang lebih terstruktur, Indonesia dapat mengurangi angka residivisme dan menciptakan kebijakan hukum yang lebih humanis tanpa mengurangi efek jera bagi pelaku kejahatan narkotika. Kata kunci: Narkotika, hukum pidana, pemidanaan, rehabilitasi, perbandingan hukum.